2014
DOI: 10.1038/ejcn.2013.269
|View full text |Cite
|
Sign up to set email alerts
|

Time course of supine and standing shifts in total body, intracellular and extracellular water for a sample of healthy adults

Abstract: For TBW, 5 min appears sufficient for fluid stabilization in either position. Supine ECW and ICW stabilization require more than 30 min as does standing ECW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
3
36
0
1
Order By: Relevance
“…In healthy individuals, moving from recumbent to standing position, extracellular volume increases while intracellular water decreases (39). While standing up, gravitational forces exert pressure on the liquid column of the body and, consequently, hydrostatic pressure increases in the lower limbs (40).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, moving from recumbent to standing position, extracellular volume increases while intracellular water decreases (39). While standing up, gravitational forces exert pressure on the liquid column of the body and, consequently, hydrostatic pressure increases in the lower limbs (40).…”
Section: Discussionmentioning
confidence: 99%
“…When upright, more fluid accumulates in the legs compared with the recumbent position. Studies in healthy subjects have suggested that whereas the measurement of TBW can be reliably performed a few minutes after changing posture, measurements of ECW and ICW should preferably be delayed to obtain greater reproducibility . There are no comparable published studies in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…We allowed time for changes in blood flow and electrolyte shifts to re-equilibrate at the end of the dialysis session [27], and also the potential effect of a change in posture [28], so that when we repeated up to 4 measurements post HD, we found no significant differences. Unlike with some other BIS devices, the electrodes remained in place during the dialysis session [29], and no electrode had to be replaced, thereby eliminating error due to changes in electrode position.…”
Section: Discussionmentioning
confidence: 99%